Ingenious vehicular system to evade collisions - Sridhar, R.; Nema, Aditya; Nalin, Anshul; Rai, Ankur (International Journal of Engineering and Technology, 2017)
Driver’s response is indispensable in the aversion of collisions and in stringent circumstances. WiB-IVS (Wireless Broadcast Intelligent Vehicular System) is a proposed design for Intelligent Vehicular Systems enabling Vehicle to Infrastructure (V2I) communication for effectuating an interconnected network of vehicles for easier and faster information sharing in order to prevent collisions. The system centralizes on driver’s response and thus aims to bring extrinsic information to the driver, stimulating situational awareness. An indication system fulfils this purpose and helps the driver respond to the scenario ahead. Information transmission is facilitated by communication between vehicle and broadcasting station based on User Datagram Protocol (UDP). The design approach caters to the problems of the collision at sharp or blind turns, offsite intersections and those occurring due to low visibility in extreme weather conditions such as fog. A pilot model design to test for the effectiveness of the proposed system architecture is also put forth in this paper. The pilot test results confirm the system’s rapid response and its key potential for the future.